Pengembangan Sistem Informasi Rekomendasi Wisata Kotawaringin Timur Berbasis Web MenggunakanMetode Item-Based Collaborative Filtering - Minarni Minarni; Sigit Sigit (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
Kotawaringin Timur Regency has many tourist objects and is rich in arts and culture spread in several sub-districts. Efforts to increase the promotion of KOTIM tourism continue to be carried out with the support of the application of technology, one of which is smart tourism. Prospective tourists tend to use internet technology to find information on tourist attractions they want to visit, rather than using the services of agents or travel agencies. Prospective tourists who want to visit East Kotawaringin need information and recommendations that are accurate, fast and economical. Recommendation systems have been widely used in the business world to help provide recommendations for various products. Therefore, a recommendation system is also used to generate tourist recommendations in East Kotawaringin using the Item-Based Collaborative Filtering method which utilizes rating data by visitors based on their travel experience. This system is in the form of a website where users can provide a rating for every tour in East Kotawaringin. Among the 35 tours in East Kotawaringin, as many as 7 tours are used in the recommendation system. These tours are Ujung Pandaran Beach, Red Kalap Gadur Waterfall, Jelawat Fish Tourism Icon, Balanga Roundabout, KOTIM Cultural Miniature Park, Satiruk Beach and Betang Tumbang Gagu. The result of the use of this recommendation system is the display of a tourist recommendation page that can be accessed by the user in the form of tours that have the highest rating equipped with detailed information on supporting tourism facilities.Keywords : Recommendation system, collaborative filtering method, tourism, East KotawaringinÂ